Repeated aspiration and sclerotherapy to manage recurrent spinal epidermoid cyst - Neyaz, Zafar (BMJ Case Rep, 2021)
Spinal epidermoid cysts are rare lesions and epidermoid cyst in intramedullary location is even rarer. Surgical excision is the mainstay of treatment; however, in cases of recurrence, repeat surgery becomes quite difficult. Treatment of recurrent intramedullary epidermoid cyst by surgery alone is a challenge. We managed one such rare case with repeated aspiration and sclerotherapy. Here, we have highlighted hypertonic saline sclerotherapy as a promising tool to treat recurrent spinal epidermoid cysts.